Gamma knife radiosurgery for arteriovenous malformations: general principles and preliminary results in a Swiss cohort (Swiss Medical Weekly, 2018)
INTRODUCTION Arteriovenous malformations (AVMs) are a type of vascular malformation characterised by an abnormal connection between arteries and veins, bypassing the capillary system. This absence of capillaries generates an elevated pressure (hyperdebit), in both the AVM and the venous drainage, increasing the risk of rupture. Management modalities are: observation, microsurgical clipping, endovascular treatment and radiosurgery. The former can be used alone or in the frame of a multidisciplinary approach. We review our single-institution experience with gamma knife radiosurgery (GKR) over a period of 5 years. MATERIALS AND METHODS The study was open-label, prospective and nonrandomised. Fifty-seven consecutive patients, benefitting from 64 GKR treatments, were included. All were treated with Leksell Gamma Knife Perfexion (Elekta Instruments, AB, Sweden) between July 2010 and August 2015. All underwent stereotactic multimodal imaging: standard digital subtraction angiography, magnetic resonance imaging and computed tomography angiography. We report obliteration rates, radiation-induced complications and haemorrhages during follow-up course. RESULTS The mean age was 46 years (range 13–79 years). The mean follow-up period was 36.4 months (median 38, range 12–75 months). Most common pretherapeutic clinical presentation was haemorrhage (50%). The most common Pollock-Flickinger score was between 1.01 and 1.5 (46%) and Spetzler-Martin grade III (46%). In 39 (60.1%) of cases, GKR was performed as upfront therapeutic option. The mean gross target volume (GTV) was 2.3 ml (median 1.2, range 0.03–11.3 ml). Mean marginal dose was 22.4 Gy (median 24, range 18–24 Gy). The mean prescription isodose volume (PIV) was 2.9 ml (median 1.8, range 0.065–14.6 ml). The overall obliteration rates (all treatments combined) at 12, 24, 36, 48 and 60 months were 4.8, 16.9%, 37.4, 63.6 and 78.4%, respectively. The main predictive factors for complete obliteration were: higher mean marginal dose (23.3 vs 21.0 Gy), lower GTV (mean 1.5 vs 3.5 ml) and absence of previous embolisation (at 60 months 61.8% prior embolisation compared with 82.4% without prior embolisation) (for all p